University of Pennsylvania Radiocarbon Dates, IX - Stuckenrath, Jr. Robert (1966)
spez. 348-351: Iran (Agrab Tepe, Hasanlu Tepe, Rezaiyeh Road Tepe, Tall-i-Bakun, Tall-i-Ghazir, Tall-i-Iblis, Susa); 352-353: Turkey (Gordion, Karataş).